Caracterização funcional dos linfócitos B1a na imunidade inata durante a infecção por Trypanosoma cruzi - Bruno Galvão Filho (2013)
Chagas disease affects approximately 8 million people in Latin America. There are many studies about Acquired and Innate Immunity against the parasite in a murine model, some of which demonstrate the importance of antibody production against the parasite. However, in addition to antibodies, B cells are capable of producing cytokines and their role in this context is largely unexplored in diseases caused by protozoa. In this work it was shown that cells B1, prevailing into peritoneal cavity of C57BL/6 mice are powerful producers of IL-10 when activated by oligonucleotide CpGs derived from Trypanosoma cruzi (in vitro). However B1 cells produce low levels of TNF- and IL-6. Furthermore, we demonstrated that infection of mice with CL strain of T. cruzi or in vivo stimulation with CpG B344 derived from parasite activates B1 cells from peritoneal cavity leading to an increase in the expression of costimulatory molecules. Subsequently, we evaluated subpopulations of cells B1 (B1a and B1b) and although both cells were sensitive to stimulation with agonists of TLRs, we conclude that B1a cells are the major producers of IL-10 in peritoneal cavity, mainly because they are prevailing in number when compared to cells B1b. In this work, we conclude that B1 cells are the first cells to produce IL-10 in Trypanosoma cruzi infection, therefore have an important regulatory role in this model before the activation of T cells producing IL-10 and may contribute to part of this production after activation of T cells in the spleen.